A cluster analysis of attitudes to English in Germany and the Netherlands. Issue 4 (12th November 2018) - Edwards, Alison; Fuchs, Robert
Abstract: Although English is becoming increasingly entrenched in Western Europe, large‐scale comparative studies of attitudes among the general public to this development are scarce. We investigate over 4, 000 Dutch and Germans' attitudes towards English based on responses to an attitudinal questionnaire. Respondents saw English as a useful additional language, but not generally as a threat to their national language. Using k‐means, an unsupervised clustering algorithm, we identified two attitudinal groups per country. Respondents with positive attitudes towards English, regardless of nationality, tended to be younger, urban, better educated and more proficient in English than their compatriots with more negative views of English. These within‐country differences outweighed between‐country ones, for example, that Germans were more confident in the status of their L1, whereas Dutch showed signs of 'English fatigue'. The findings thus appear to confirm the previously identified divide between elite 'haves' versus 'have‐nots' of English.